Aulas-passeio: contribuições para aprendizagens em ciências - Oliveira, Angelina dos Santos (2016)
The field-classes allow to create new learning spaces, avoiding methodologies that keep students trapped in the classroom, teaching strategies seeking to awaken in students cooperation and pleasure for knowledge. These classes are geared to the interest of students, from their realities, with the main objective of the motivation of students for learning. In science education, still remain an educational format where the teacher teaches and the student listens causing lack of interest in the students. It is necessary to find new ways of learning, generating desire for knowledge. In this research the ride-classes were used as teaching methodology, with students from 7th year of elementary school. The activities were held outside the school in Bastiões district, Itapipoca Municipality and on a trip to the Nucleo Regional de Ofiologia in Fortaleza. We seek to verify the understanding of the construction of knowledge by the student, taking into account the insights derived from their impressions and verbal and visual assessments, based on the methodology proposed by Freinet. We also observed the perception of the spaces where they live in relation to animals, plants and environment. As an educational product, we designed a guide to drive classes, whose main objective was to provide the teacher a proposed activity that guides students during achievements of these activities in natural environments. The research, usedqualitative analysis, trying to understand the phenomena occurring, words and the sentiments expressed by the students. Experience activities combined with the knowledge of local culture, are much more meaningful to students, who learn when they produce.